CIRCULAR-SHAPED OBJECT DETECTION IN LOW RESOLUTION SATELLITE IMAGES - A. Tadros; S. Drouyer; R. Grompone von Gioi; G. Facciolo; L. Carvalho (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2020)
Circle and ellipse detection have been a widely discussed topic among the computer vision community. Applying circle detection methods to satellite images can bring valuable information on urban or industrial areas. A limitation of such methods lies in the resolution of the object to detect. The smaller they are in the image, the harder it becomes to detect them accurately. In this paper, we explore several circle detection methods adapted to low resolution satellite images. An algorithm based on level-lines detection and classification will be presented in this paper along with other well known algorithms. The methods are evaluated in the context of oil tank detection in Sentinel-2 images where those circular objects can have an observed diameter as small as 2 pixels.